Use of steel slag and recycled concrete in GeoBarrier system for slope stabilization - Abishev, Rezat; Satyanaga, Alfrendo; Guney, Mert; Lim, Aswin; Kim, Jong (Frontiers in Built Environment, 2025)
Improving slope stability against rainfall-induced slope collapses is a current area of study interest in geotechnical structure design for climate change mitigation. The GeoBarrier system (GBS) concept used recycled concrete and steel slag to avoid these kinds of failures. The present study investigated the practicability of incorporating recycled concrete and steel slag, two types of recycled materials, into the GBS design. Extensive experimental investigations were conducted to determine the index properties and hydraulic characteristics, including permeability functions, soil-water characteristic curves (SWCCs), and unsaturated shear strength parameters of steel slag and recycled concrete. A finite element transient seepage analysis and limit equilibrium slope stability study were conducted to evaluate the impact of precipitation on the pore water pressure profile of the slope and its stability under rainfall circumstances, respectively. According to the findings, no breakthrough into the steel slag, a coarse-grained layer within the GBS, was observed. Based on the pore-water pressure profiles and the variation in the factor of safety (FOS) over time, steel slag and recycled concrete were found to be applicable for use as coarse- and fine-grained layers in the GBS, respectively. The incorporation of these waste materials facilitated the slope protection against infiltrated rainwater into the slope and increased the FOS for a slope with a height of 10 m and a slope angle of 70°.